“Foreigners in Town”: Leisure, Consumption, and Cosmopolitanism in Late-Nineteenth and Early-Twentieth Century Tillsonburg, Ontario - Beausaert, Rebecca (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2012)
At the turn of the twentieth century, the small town of Tillsonburg, Ontario contained a population that was over eighty-six percent Anglo-Celtic in origin. Increasingly, however, local leisure activities began to incorporate “ethnic” food, dress, and mannerisms so that citizens could momentarily become “foreigners” and “consume” knowledge of other nations and peoples. Two of the more notable venues where participants acted out racialized identities—the “Garden Party of the Nations” and the Ladies’ Travel Club—showcase desires to consume markers of foreignness while concurrently displaying an acceptance of these cultures. Using Tillsonburg as a case study, this article examines how engaging with the “foreign” in patterns of leisure and consumption was a way for citizens (and women in particular) to convey an air of cosmopolitanism and cultural refinement in the face of critiques that small towns were insular and unsophisticated. Their cultural appropriations, however, represent grossly distorted understandings of races, ethnicities, and cultures that existed outside their Euro-Canadian one. Though efforts by Tillsonburg’s populace to appear more cosmopolitan were grounded in a desire to expand understandings of “the foreign,” this occurred only on their own terms and in controlled spaces.